Use Of Strategic Management Accounting by Large Manufacturing Companies in Bujumbura - Bellini Munezero; Puji Handayati; Satia Nur Maharani (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this research was to determine the types and extent to which strategic management accounting systems are used by manufacturing companies in Bujumbura. The primary goal of this research is to determine the kind and extent to which strategic management accounting systems are implemented in the manufacturing sector of Bujumbura. Primary data was gathered to attain this goal. Data was collected using a quantitative technique based on descriptive analysis. According to the findings of this study, significant companies in Bujumbura have primarily embraced strategic management accounting methodologies. Strategic planning and budgeting, as well as strategic costing, are the most commonly used strategies. Other strategic management accounting strategies, such as quality costing and customer accounting, do not appear to have been used a lot